Efecto de la proporción de agua, lactosuero y quinua (chenopodium quinoa w.) blanca germinada en la aceptabilidad general de una bebida fermentada utilizando cultivo láctico comercial - Reyna Benites, Lysbeth Yanina (2017)
The aim of this study was to determine the effect of the proportion of water, whey and quinoa (Chenopodium quinoa W.) White germinated in the general acceptability of a fermented beverage using Lactic Commercial Farming (BFCLC). Was possible to determine the effect of the water content (A), whey (L) and quinoa (Q) (Chenopodium quinoa W.) germinated in the overall acceptability of a BFCLC by response surface, a cubic function was obtained: 5.61718 * Q + 4.40468 * a + 7.21491 * L + 5.14372 * Q * a + 0.66417 * Q * L + 3.58917 * a * L + 34.98088 * Q * a * L (R2 = 98.57% and Radj = 95.73%), determining that the acceptable optimum range has the following concentrations: 26% - 28% of quinoa, 26% - 28% water and 38% - 44% whey within these limits is the maximum values for acceptability ie 7.5 - 8 ; finally the protein efficiency BFCLC prepared with the following formulation 38% quinoa, 38% water and 52% whey, being the value of the efficient relationship protein (PER) was 2.24, determined the biological value (VB) of 94.56%, net protein utilization (NPU) of 89.15% and 94.28% digestibility; so it is concluded that the proteins contained in this product are of good quality and can be used as a substitute for any milk drink.